Review of the Epidemiological Situation on Ixodic Tick-Borne Borreliosis in the Russian Federation in 2010–2020 and Prognosis for 2021 - S. A. Rudakova; N. A. Pen’evskaya; A. I. Blokh; N. V. Rudakov; D. V. Trankvilevsky; D. A. Savel’ev; O. E. Teslova; N. E. Kaneshova (Проблемы особо опасных инфекций, 2021)
Objective was to analyze the epidemiological situation on Ixodidae tick-borne borreliosis (ITBB) in the constituent entities of the Russian Federation in the dynamics over the period of 2010–2020, taking into account the features of the year 2020, associated with the spread of COVID-19, and to forecast the development of the epidemic process for 2021. In 2020, 4180 cases of ITBB were registered in the Russian Federation, which is 1.93 times less than in 2019 and 1.73 times less than the long-term average annual figure for the previous 10 years. A significant decrease was noted in all federal districts (FD), with the exception of the Central FD, where more than half of all cases occurred. Compared to 2019, 75 out of 78 subjects experienced a decrease in the incidence rate in 2020, while in 56 entities that decrease was statistically significant. The multiplicity of the decrease in the incidence of ITBB in 2020 for all FD was significantly greater than the multiplicity of the decrease in the frequency of contacts of the population with ticks. Infection of Ixodidae ticks of various species with borrelia in natural foci in 2020 was statistically significantly higher than in 2019. Probably, the decrease in the registered incidence of ITBB against the background of the COVID-19 pandemic is due not only to a decrease in the intensity of contacts of the population with natural foci, but also to a sharp redistribution of the volume of inpatient and outpatient medical care in favor of COVID-19 patients. Given the high degree of significance of the identified trends in the dynamics of the epidemic ITBB process during 2010–2020, there is reason to expect an increase in the incidence in the Bryansk, Voronezh, Ryazan, Tula and Saratov regions in 2021, which requires special attention in terms of strengthening preventive measures and monitoring of the activity and structure of natural foci. In the rest of the entities of the Russian Federation, provided that the volumes of preventive measures are maintained on the same level and in the absence of abnormal natural and climatic phenomena, preservation or a slight reduction in the incidence of ITBB is likely to occur in the short term. At the same time, despite the tense situation regarding the new coronavirus infection, there is an obvious need to draw close attention to the problems of diagnosis and prevention of natural focal infections.